Design and Implementation of the Mobile Fire Alarm System Using Wireless Sensor Networks - Muheden, Kaman; Erdem, Ebubekir; Vancin, Sercan (Ieee, 2016)
The surveillance of home or industrial places through sensors and the prevention of problems via prediction are of vital importance for the safety of these areas. This paper shows how to increase wireless sensor network (WSN) techniques by composing new design methods and improved a low-cost industrial and home safety systems. So as to guarantee and present accurate solutions to the system, not only temperature and humidity sensors but also flame and gas sensors were used in this study. The design of simple hardware circuit allows every user to utilize this wireless home safety system. A notification was used as a method of informing users related to system. The installed Arduino device which was programmed with Android Studio takes received gas, flame, the temperature, and humidity signals from the sensors. In order to pre-monitor the capability of occurrence of a fire, when it detects that the collected data with control levels exceed a predefined threshold it will enable the communication with WIFI network and send the notification alarm message to the mobile users.
17th IEEE International Symposium on Computational Intelligence and Informatics (CINTI) -- NOV 17-19, 2016 -- Budapest, HUNGARY
Keywords: Fire Alarm System; WIFI; Notification; WSN